Geochemical evaluation of the hydrocarbon prospects of carbonaceous shale and coal of Barail Group, Upper Assam Basin. (2018) - Sharma, Arpita; Phukan, Sarat; Saikia, Binoy K.; Baruah, Bimala P.
The Upper Assam Basin is an important onshore petroleum province in India. The petroleum generation potential of Barail coal and carbonaceous shale in the different oil fields has been assessed to determine the source rock quality of the coal/shale unit or the argillaceous unit in the Upper Assam Shelf of Barail Group. Organic geochemical analyses involving elemental analysis, TOC and Rock-Eval pyrolysis were carried out on some selected subsurface core samples from different oil fields of Upper Assam to characterise their sedimentary organic matter. Rock-Eval pyrolysis showed good organic carbon richness, i.e., TOC (1.00%-69.21%), thus indicating good generative potential for petroleum. The Tmax data span of the studied samples is 396°C-433°C. Low Tmax values (<430°C) of the studied samples indicate that the organic matter in the coal and carbonaceous shale samples of Barail strata are either immature or less mature with respect to liquid hydrocarbon generation. The Rock-Eval pyrolysis results indicate the mixed type II and III kerogen, which is of good source rock quality, but thermally immature to generate petroleum. [Received: February 9, 2016; Accepted: September 20, 2016]